2009
DOI: 10.1021/la9015299
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Zirconium Titanium Oxides. Part 3. Synthesis and Adsorption Properties of Unfunctionalized and Phosphonate-Functionalized Hierarchical Polyacrylonitrile-F-127-Templated Beads

Abstract: A method is presented for the preparation of zirconium titanate mixed oxides in bead form having hierarchical pore structure. This method entailed the use of both preformed polyacrylonitrile (PAN) polymer beads and surfactants as templates. The templates were removed by calcination at temperatures below about 500 degrees C, resulting in mixed oxide beads with trimodal pore size distributions and interconnected pores. The pore size distributions as determined using nitrogen adsorption-desorption showed clear ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 50 publications
0
62
0
Order By: Relevance
“…This is desirable as hierarchical porosity often improves mass transport properties and increases the number of readily available reaction sites. 15 Two types of hysteresis are also evident in Fig. 2.…”
mentioning
confidence: 80%
“…This is desirable as hierarchical porosity often improves mass transport properties and increases the number of readily available reaction sites. 15 Two types of hysteresis are also evident in Fig. 2.…”
mentioning
confidence: 80%
“…Recently it has also been found that ATMP coordinates well to surfaces of mesoporous materials and successfully used as a metal adsorbent material for Cu(II), Hg(II), Cd(II), U(VI), and other radionuclides [131][132][133]. Depending on the interaction type, ATMP ligands surrounding a metal center ideally coordinate with both deprotonated phosphoryl oxygens and an N-central donor atom, creating an octahedral coordination structure (Fig.…”
Section: Ion-exchange Materials With Chelating Anchor Groups: Polyphomentioning
confidence: 99%
“…The titania–zirconia hybrids have affinity to phosphopeptides so that concentration of the phosphopeptides on the surface was achieved [ 111 ]. Sizgek et al reported the preparation of millimeter-sized spherical nanoporous titania–zirconia particles with a variable Zr/Ti ratio [ 112 114 ]. The titania–zirconia hybrid particles were easy to handle owing to their large size, and the authors suggested that they can be used for adsorbing vanadium and uranium species.…”
Section: Synthesis Of Oxide-based Well-defined Particlesmentioning
confidence: 99%